Longitudinal Findings of MRI and PET in West Syndrome with Subtle Focal Cortical Dysplasia - Sakaguchi, Y.; Kidokoro, H.; Ogawa, C.; Okai, Y.; Ito, Y.; Yamamoto, H.; Ohno, A.; Nakata, T.; Tsuji, T.; Nakane, T.; Kawai, H.; Kato, K.; et al. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Despite the development of neuroimaging, identification of focal cortical dysplasia remains challenging. The purpose of this study was to show the longitudinal changes of MR imaging and FDG-PET in patients with West syndrome and subtle focal cortical dysplasia.MATERIALS AND METHODS: Among 52 consecutive patients with West syndrome, 4 were diagnosed with subtle focal cortical dysplasia on 3T MR imaging. MR imaging and PET findings were evaluated longitudinally at onset and at 12 and 24 months of age.RESULTS: At the onset of West syndrome, MR imaging demonstrated focal signal abnormalities of the subcortical white matter in 2 patients. In the other 2 patients, focal subcortical high-intensity signals became visible on follow-up T2WI as myelination progressed. PET at onset showed focal cortical hypometabolism in 3 patients, with 1 of these patients also having focal hypermetabolism and 1 having normal findings. On PET at 24 months, hypometabolism persisted in 2 patients and disappeared in 1, and hypermetabolism disappeared in 1. In 1 patient with normal MR imaging and PET findings at onset, focal hyperintensity and hypometabolism first appeared at 24 months of age. The findings on MR imaging and PET in these patients evolved differently with brain maturation and the clinical course.CONCLUSIONS: Subtle focal cortical dysplasia can be undetectable on MR imaging at the onset of West syndrome and is not always accompanied by hypometabolism or hypermetabolism on PET. Longitudinal MR imaging and PET studies may be useful for detecting such lesions. Even in West syndrome with a congenital structural abnormality, PET findings evolve differently with brain maturation and the clinical condition.EEGelectroencephalographyFCDfocal cortical dysplasiaWSWest syndrome